(untitled) (Journal of Entrepreneurship and Business, 2022)
The current research goal is to examine the impact of trust on the intention to use e-wallet services. Using the technology acceptance model (TAM) the study investigated four variables which were privacy and security, perceived ease of use, perceived usefulness, and trust for intention to use e-wallets. The study employed the quantitative research design with non-probability sampling using the purposive sampling method for data collection purposes. Through the Google survey form data were collected from the University of Malaya undergraduate students (N=150). The study applied the partial least square (PLS) tool using SmartPLS 3.0 to analyze the data. The outcome of the research found that all four variables had a positive significant connection to the intention to use e-wallet services. The results indicate that the service e-wallet is important among young generations because this electronic payment service is convenient to make payments as well as transactions from anywhere, besides increasing the e-wallet facilities among users, service providers should focus on users’ privacy and security.